Characteristics Influence of Corporate Governance and Firm Performance Against Tax Avoidance (Empirical Study On Dan Baverage Company Listed on the Indonesia Stock Exchange Year 2012 to 2015) - Siti Nurlaela, Meilina Tri Astuti, Kartika Hendra Titisari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to empirically examine the influence of corporate governance andcorporate characteristics on tax evasion. This analysis uses the independentvariable is institutional ownership, independent directors, audit committee,profitability (ROA) and leverage (DER). The dependent variable is tax evasion.Examples of food and beverage research company listed on the Indonesia StockExchange in 2012-2015. The research method using purposive sampling methodand statistical using multiple linear regression analysis. Samples were obtainedfrom 11 companies with a term of 4 years resulted in 44 samples. The results ofthis study indicate institutional ownership, independent directors and auditcommittee did not significantly affect the tax evasion,Keywords: institutional ownership, independent directors, audit committee profitability(ROA), leverage